Complexity and postmodernism : understanding complex systems - Cilliers, Paul, 1956-2011 (Routledge, 1998)
In Complexity and Postmodernism, Paul Cilliers offers us a unique approach to understanding complexity and computational theory by integrating postmodern theory (like that of Derrida and Lyotard) into his discussion.
Keywords: Complexity (Philosophy); Computational complexity.; Postmodernism.; Complexité (Philosophie); Complexité de calcul (Informatique); Postmodernisme.; PHILOSOPHY -- Metaphysics.; Computational complexity; Postmodernism